2017
DOI: 10.1002/lary.26908
|View full text |Cite
|
Sign up to set email alerts
|

Early Stage olfactory neuroblastoma and the impact of resecting dura and olfactory bulb

Abstract: 4. Laryngoscope, 128:1274-1280, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…For early stage disease confined to the sinonasal cavity, single modality treatment with surgery yields a high degree of oncological control. 20 However, for advanced disease, multimodality approach is preferred. Due to high local failure rate, surgical resection followed by PORT is adapted by many institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For early stage disease confined to the sinonasal cavity, single modality treatment with surgery yields a high degree of oncological control. 20 However, for advanced disease, multimodality approach is preferred. Due to high local failure rate, surgical resection followed by PORT is adapted by many institutions.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal treatment approach for ONB is not uniform due to the few number of published cases and absence of prospective studies. For early stage disease confined to the sinonasal cavity, single modality treatment with surgery yields a high degree of oncological control 20 . However, for advanced disease, multimodality approach is preferred.…”
Section: Discussionmentioning
confidence: 99%
“…The present series counted a total of 112 cases of ONB, with 10-year OS and DFS of 90.9% and 69.1%, respectively, comparing equal or better with other series [30][31][32]. According to the literature, most recognized negative prognostic factors for ONB are advanced Kadish stage, high Hyams grade, the presence of nodal metastasis and infiltrated postoperative surgical margins [30,31,[33][34][35][36].…”
Section: Olfactory Neuroblastoma (Onb)mentioning
confidence: 50%
“…Meerwein CM et al [12] claimed that surgery alone is an equivalent alternative to combined treatment in early-stage ONB patients. Mays AC et al [13] reported that PORT did not impact disease-free survival in early-stage ONB. An NCDB study by Carey RM et al [14] used patients with stage A and B as a combined stage for survival analysis, and the results showed that surgery alone, compared with PORT, had no signi cant difference in survival.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection followed by postoperative radiotherapy (PORT) is considered the primary option for ONB patients [3]. However, controversy exists regarding whether early-stage ONB patients can bene t from PORT to improve their survival [2,[10][11][12][13][14]. Moreover, previous studies demonstrated that PORT was not effective in improving long-term survival [15].…”
Section: Introductionmentioning
confidence: 99%